The Composition of Fiscal Adjustment and Growth : Lessons from Fiscal Reforms in Eight Economies - Mackenzie, George; Gerson, Philip; Orsmond, David (Washington, D.C. : International Monetary Fund, 1997)
This study examines the composition of fiscal adjustment - tax and expenditure policies and administrative procedures, and some aspects of public enterprise reform - in a sample of eight countries (Bangladesh, Chile, Ghana, India, Mexico, Morocco, Senegal, and Thailand) during a period of fiscal reform (usually 1978-93), to determine whether and to what extent the fiscal reforms fostered growth during the adjustment period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet